Ethylene positively regulates Cd tolerance via reactive oxygen species scavenging and apoplastic transport barrier formation in rice. (1st June 2022) - Chen, Haifei; Zhang, Quan; Lv, Wei; Yu, Xiaoyi; Zhang, Zhenhua
Abstract: Ethylene regulates plant root growth and resistance to environment stress. However, the role and mechanism of ethylene signaling in response to Cd stress in rice remains unclear. Here, we revealed that ethylene signaling plays a positive role in the resistance of rice to Cd toxicity. Blocking the ethylene signal facilitated root elongation under normal conditions, but resulted in severe oxidative damage and inhibition of root growth under Cd stress. Conversely, ethylene signal enhancement by EIN2 overexpression caused root bending, similar to the response of roots to Cd stress, and displayed higher Cd tolerance than the wildtype (WT) plants. Comparative transcriptome analysis indicated EIN2-mediated upregulation of genes involved in flavonoid biosynthesis and peroxidase activity under Cd stress. The synthesis of phenolic acids and flavonoids were positively regulated by ethylene. Thus, the ein2 ( ethylene insensitive 2 ) mutants displayed lower ROS scavenging capacity than the WT. Moreover, a significant increase in Cd accumulation and relatively increased apoplastic flow were observed in the root apex of the ein2 mutant compared with the WT plants. Overall, EIN2-mediated Cd resistance in rice is mediated by the upregulation of flavonoid biosynthesis and peroxidase activity to induce ROS scavenging, and apoplastic transport barrier formation reduces Cd uptake. Graphical abstract: Image 1 Highlights: Ethylene signal blocking caused severe oxidative damage to roots under Cd stress. Ethylene signal positively regulated PRX activity to scavenge ROS under Cd stress. EIN2-mediated Cd resistance is mediated by upregulation of flavonoid synthesis. EIN2-mediated apoplastic transport barrier formation in roots reduced Cd uptake.